Design and in situ synthesis of a Cu-based porous framework featuring isolated double chain magnetic character - Dey, Chandan; Das, Raja; Saha, Binoy Krishna; Poddar, Pankaj; Banerjee, Rahul (Chemical Communications, 2011)
A Cu-based double chain MOF was synthesized in hydrothermal conditions using an in situ ligand formation method. This double chain MOF shows temperature dependent ferromagnetic (long range ordering) and antiferromagnetic (intra double chain) coupling. The magnetic behaviour originating from the individual double chain remains almost same even after structural collapse due to the removal of guest water molecules.

Decoding the morphological diversity in two dimensional crystalline porous polymers - Halder, Arjun; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Density functional calculations; Morphology

Dissolvable metallohydrogels for controlled release: evidence of a kinetic supramolecular gel phase intermediate - Saha, Subhadeep; Bachl, Jurgen; Kundu, Tanay; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
Two metallohydrogels based on an amino acid-based ligand and Zn(II) salts were synthesized. These hydrogels show an uncommon, reversible, time-dependent transformation from the opaque to transparent state. These hydrogels also exhibit gradual dissolution in water (pH <= 7) over time. A water-soluble stimulant, caffeine, could be in situ loaded into the hydrogels and slowly released during dissolution.

Distinctive PdCl2-mediated transformation of Fe-based metallogels into metal-organic frameworks - Aiyappa, Harshitha Barike; Saha, Subhadeep; Garai, Bikash; Thote, Jayshri; Kurungot, Sreekumar; Banerjee, Rahul (Crystal Growth & Design, 2014)
Simple, efficient conversion of viable Fe3+-based metallogels into Fe-metal-organic frameworks (MOFs) has been achieved by PdCl2-mediated gel degradation. The metallogels and the resulting MOFs have been characterized, and a probable mechanism for the event has been elucidated.

Decoding the morphological diversity in two dimensional crystalline porous polymers by core planarity modulation - Halder, Arjun; Kandambeth, Sharath; Biswal, Bishnu P.; Kaur, Gagandeep; Roy, Neha Chaki; Addicoat, Matthew A.; Salunke, Jagadish K.; Banerjee, Subhrashis; Vanka, Kumar; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Angewandte Chemie - International Edition, 2016)

Dual nanomechanics in anisotropic porous covalent organic framework janus-type thin films - Mohata, Shibani; Dey, Kaushik; Bhunia, Surojit; Thomas, Neethu; Gowd, E. Bhoje; Ajithkumar, Thalasseril G.; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Empowered by crystalline ordered structures and homogeneous fabrication techniques, covalent organic frameworks (COFs) have been realized with uniform morphologies and isotropic properties. However, such homogeneity often hinders various surface-dependent properties observed in asymmetric nanostructures. The challenge remains to induce heterogeneity in COFs by creating an asymmetric superstructure such as a Janus thin film. In this regard, we propose a versatile yet straightforward interfacial layer-grafting strategy to fabricate free-standing Janus-type COF-graphene thin films. Herein, two-dimensional graphene sheets were utilized as the suitable grafter due to the possibility of noncovalent interactions between the layers. The versatility of the approach was demonstrated by fabricating two distinct Janus-type films, with the COF surface interwoven with nanofibers and nanospheres. The Janus-type films showcase opposing surface morphologies originating from graphene sheets and COF nanofibers or nanospheres, preserving the porosity (552-600 m(2) g(-1)). The unique surface chemistries of the constituent layers further endow the films with orthogonal mechanical properties, as confirmed by the nanoindentation technique. Interestingly, the graphene sheets favor the Janus-type assembly of COF nanofibers over the nanospheres. This is reflected in the better nanomechanical properties of COFfiber-graphene films (E-gra(phene) = 300-1200 MPa; E-COF( )= 15-60 MPa) compared to the COFsphere-graphene films (E-gra(phe)ne = 11-14 MPa; E-CO(F )= 2-5 MPa). These results indicate a direct relationship between the mechanical properties and homo/heterogeneity of Janus-type COF films.